POSITIVE IMPACT OF INFUSION WITH LEVOSIMENDAN ON THE ELDER PATIENTS (60-75 YEARS OLD) WITH LOWER EJECTION FRACTION OF THE LEFT VENTRICLE (< 50%) IN THE PERI-OPERATIVE PERIOD IN NON-CARDIAC SURGERY - Yu. V. Ubasev; Yu. V. Skripkin; T. S. Zabelina; V. A. Sungurov; V. V. Lomivorotov; D. N. Marchenko; V. V. Likhvantsev (Вестник анестезиологии и реаниматологии, 2018)
Pre-surgery infusion with levosimendan with the rate of 0.05–0.1 mkg*kg-1 min-1 to the elder patients (60–75 years old) with lower ejection fraction of the left ventricle (less than 50%) results in its increase by 16.7% (p < 0.01), cardiac index – by 10.3% (p >< 0.01) and reduction of NT-proBNP level in blood by 24.1% (p >< 0.1) in 24 hours after the medication infusion start. The changes persist for at least 24 hours after the surgery. Key words: levosimendan, cardiac failure, peri-operative period, pre-surgery preparation, cardiac surgery, reduction of NT-proBNP level.>< 0.01), cardiac index – by 10.3% (p< 0.01) and reduction of NT-proBNP level in blood by 24.1% (p < 0.1) in 24 hours after the medication infusion start. The changes persist for at least 24 hours after the surgery. Key words: levosimendan, cardiac failure, peri-operative period, pre-surgery preparation, cardiac surgery, reduction of NT-proBNP level.>< 0.1) in 24 hours after the medication infusion start. The changes persist for at least 24 hours after the surgery.